Shelter supplies - United States. Office of Civilian Defense (Fallout Protection: What to Know and Do About Nuclear Attack, 1961)
Recommended supplies to have on hand for fallout shelter in case of nuclear attack.
Keywords: Radioactive fallout; Civil defense; United States. Government Printing Office; United States. Office of Civilian Defense